2014
DOI: 10.3390/polym6020443
|View full text |Cite
|
Sign up to set email alerts
|

CFRP-Strengthening and Long-Term Performance of Fatigue Critical Welds of a Steel Box Girder

Abstract: Empa's research efforts in the 1990s provided evidence that a considerable increase of the fatigue strength of welded aluminum beams can be achieved by externally bonding pultruded carbon fiber reinforced polymer (CFRP) laminates using rubber-toughened epoxies over the fatigue-weak welding zone on their tensile flange. The reinforcing effect obtained is determined by the stiffness of the unidirectional CFRP laminate which has twice the elastic modulus of aluminum. One can therefore easily follow that an unstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…It was found that the predicted fatigue life was consistent with the experimental result. Koller et al [ 17 ] identified an adhesive system suitable for achieving a high fatigue strength in a carbon-fiber-reinforced polymer patch. The results showed that the compressive nominal stress promoted the crack closure effect.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the predicted fatigue life was consistent with the experimental result. Koller et al [ 17 ] identified an adhesive system suitable for achieving a high fatigue strength in a carbon-fiber-reinforced polymer patch. The results showed that the compressive nominal stress promoted the crack closure effect.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies investigated the use of pre-stressed CFRP laminates to strengthen steel structures. It was noticed that the use of CFRP composites for retrofitting steel structures is not very popular [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The defect of crack can also impair the bearing capacity and make the structures prone to brittle fracture. To restore the bearing capacity or retard crack propagation, CFRP plate was prestressed and patched to a steel pendulum with rectangular hollow section [13]. Scaled fatigue tests were conducted before the technique was applied to a site rehabilitation project.…”
Section: Introductionmentioning
confidence: 99%